Quantum psychology approach on enjoyment as mediator in relationship between L2 flow and engagement - Çelik, Ferdi (Frontiers in Psychology, 2025)
IntroductionQuantum psychology offers scholars a novel lens, to be preferred when Chaos/Complexity falls short of understanding the missing puzzle pieces in the complex interplay between cognitive and affective factors in second language acquisition (SLA). Adopting a quantum psychology approach, this study conceptualizes learner psychology as probabilistic and non-linear, proposing that flow, enjoyment, and engagement are dynamically entangled, akin to quantum principles of superposition and entanglement.MethodsTo test this, the study investigates the mediating role of enjoyment in the relationship between psychological flow and academic engagement among 162 high school students in artificial intelligence (AI)-assisted English as a Foreign Language (EFL) speaking and writing classes. Employing a quantitative, cross-sectional design, data were collected using a validated Psychological Flow Scale, Academic Engagement Scale, and Foreign Language Enjoyment Scale.ResultsPath analysis has revealed that psychological flow does not directly influence academic engagement; however, flow significantly predicts enjoyment, which in turn positively affects engagement. The indirect effect of flow on engagement through enjoyment was significant and indicated full mediation.DiscussionThese findings challenge linear models of flow and engagement in SLA. The results, interpreted through a quantum perspective, emphasize the importance of fostering enjoyable learning experiences to enhance engagement, particularly in technology-enhanced contexts like AI-assisted classrooms. Pedagogical implications include designing interactive, enjoyable, and optimally challenging tasks to promote flow and enjoyment to sustain learner engagement. Future studies should investigate more mediators and use longitudinal designs to clarify these evolving relationships.